Digital workflows for anchoring implants in the zygomatic bone (Research, Society and Development, 2024)
This study aims to conduct a literature review on digital workflows in the anchoring of implants in the zygomatic bone, focusing on digital planning, and to demonstrate how these technologies influence the increase in safety and predictability of the procedure. A bibliographic survey was conducted in the PubMed database, using the following descriptors in English: “dental implants” AND “zygoma” AND “bone resorption” AND “digital health”. The inclusion criteria were studies with a relevant approach to the proposed theme; while the exclusion criteria were course completion papers, articles on animals, literature reviews and articles that were not in line with the theme addressed. The study concludes that the application of digital workflows in the planning of oral rehabilitation with zygomatic implants offers significant improvements in safety and accuracy. However, the effectiveness of these technologies depends on the professional's learning curve, without excluding the importance of the surgeon's experience and skills.